Goosebumps Horrorland. #10 Help! We have strange powers! - Stine, R. L. (Scholastic New York, New York, 2009)
Jillian and Jackson freak out when they suddenly can read people's thoughts. But the trick turns to terror when the twins are stalked by a strange scientist who wants to know exactly what's on their minds. Will the twins ever lead normal lives again? Not in HorrorLand they won't. There are free meals, free games, and free falls down the DoomSlide. Someone's watching their every step. But is she friend or foe?